2014
DOI: 10.2105/ajph.2013.301733
|View full text |Cite
|
Sign up to set email alerts
|

Health and Health Risks Among Sexual Minority Women: An Examination of 3 Subgroups

Abstract: We used National Health and Nutrition Examination Survey data to examine insurance status, source of routine care, cigarette and alcohol use, and self-rated health among lesbian, bisexual, and heterosexual women who have sex with women (WSW), compared to heterosexual women who do not have sex with women. We found higher risks of being uninsured among lesbian and bisexual women, worse self-rated health among bisexual women, higher alcohol use among bisexual and heterosexual WSW, and higher smoking across all su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…57 Combined with the relative lack of bisexual-specific organizations, bisexual individuals have fewer opportunities for affiliation with “similar others”—a protective factor against negative stigma. 57,58 Given these and other findings, 5,32,59 bisexual individuals should be considered a distinct group in mental health research and intervention design.…”
Section: Discussionmentioning
confidence: 96%
“…57 Combined with the relative lack of bisexual-specific organizations, bisexual individuals have fewer opportunities for affiliation with “similar others”—a protective factor against negative stigma. 57,58 Given these and other findings, 5,32,59 bisexual individuals should be considered a distinct group in mental health research and intervention design.…”
Section: Discussionmentioning
confidence: 96%
“…That said, probabilitybased studies have quite frequently found that bisexual women differ significantly from lesbian and heterosexual women in terms of age and income, with bisexual women being significantly younger and more likely to be living in poverty. 8,9,13,22 Research on patterns of poverty within lesbian, gay, and bisexual populations also shows bisexual adults experience the highest rates of poverty, and in some cases, a higher propensity to receive public assistance. 23 The correlation between poverty and bisexual identity is an area in need of further investigation, as the health consequences of living in poverty very likely drive many of the disparities typically seen among bisexual women.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40] These findings suggest that BWSW's unique experiences with stigma and medical mistrust are likely contributing to these disparities in seeking care, even when care is clinically necessary. The emergence of new biomedical technologies that screen for and treat life threatening diseases and conditions has led to great advances in medical care, yet they are ineffective if patients are not under the care of medical practitioners to utilize these technologies.…”
Section: Resultsmentioning
confidence: 99%